PENGARUH PENDIDIKAN KESEHATAN TERHADAP PENGETAHUAN DAN KETERAMPILAN DALAM PERAWATAN PAYUDARA PADA IBU POST PARTUM DI RS Dr. OEN SURAKARTA - Sri Aminingsih; Warsini Warsini; Umi Padmiati (Sekolah Tinggi Ilmu Kesehatan Panti Kosala, 2013)
Background. Health education is a planned process of change in behavior onthe individual or community to be more self-sufficient in achieving life goals se,attitudes and community practices in maintaining and improving health.The purpose to determine the effect of health education on the knowledge andskills in the treatment of breast in women post partumMethod using pre post experimental with a total sample of 25 respondents. Theresult showed no conclusions on the effect of health education knowledge andskills in the treatment of breast in women postpartum hospital. Dr. OenSurakarta. This is evidenced by the amount of 0.01 t Î± = 9.313 and t table =2.797 for knowledge, while for the results obtained skills t Î± 0,01 = 10.303 and ttable = 2.797. This study data analysis using Paired Test.The conclusion. There pendidikanpendidikan influence the health of theknowledge and skills in the treatment of breast in women postpartum in RS Dr.Oen Surakarta.Keywords : Health education, knowledge of breast care and breast care skills